Haj - A mission of peace - Abd Razak, Dzulkifli (2006)
During the haj, every pilgrim is on the same plane, regardless of wealth or status THE world saw, at Mecca last week, what could easily be the largest demonstration of fellowship in one place. Here is where Islam presented its face of peace to the international community in a practical way, especially after the 911 tragedy, and the ensuing "war on terrorism". Never before had the image of Islam suffered so much as in recent times. It does not matter if the root word for "Islam" comes from salam which means "peace".